A New International Scheme for the Classification and Management of Clinical Outcomes Post-gastric Peroral Endoscopic Myotomy - Ichkhanian, Yervant; Salame, Marita; Wo, John M; Nowak, Thomas V; Stainko, Sarah; Saito, Akira; Siwiec, Robert M; Kais, Amr; Hwang, Joo Ha; Li, Andrew A; Yang, Juliana; Broucek, Joseph R; et al. (Clinical gastroenterology and hepatology, 2025)
BACKGROUND & AIMS: Gastric peroral endoscopic myotomy (G-POEM) is an emerging treatment for gastroparesis, but clinical outcomes can be inconsistent; hence, it is vital to enhance our management strategies for patients with clinical failure. METHODS: This was a multicenter retrospective review of patients who underwent G-POEM for refractory gastroparesis from September 2015 to November 2023. Clinical outcomes and management post-G-POEM were assessed and categorized into 4 types based on symptom improvement and gastric emptying metrics. RESULTS: Of the 482 patients, 221 (46%) underwent evaluations with pre- and post-G-POEM gastric emptying tests and were included in the study. Type 1 clinical response (clinical success with improved gastric emptying scintigraphy [GES]) was the most common outcome, occurring in 56%. This was followed by type 4 (clinical failure with no GES improvement) at 23%, type 2 (clinical failure with improved GES) at 15%, and type 3 (clinical success with no GES improvement) at 6.7%. Patients with primary clinical failure (types 2 and 4) showed significantly higher daily opioid use at 23%, compared with 7% in types 1 and 3 (P = .032). Clinical failure overall was observed in 60% during a median follow-up of 48 months, with 31% managed by pylorus-directed retreatment and 7% with gastric neurostimulator placement. In the type 1 response group, clinical success was re-established in 71% following pylorus-directed therapies, with repeat G-POEM being an independent predictor of clinical success post-re-treatment (odds ratio, 2.2; P = .02). CONCLUSION: Our study highlights the importance of post-G-POEM GES assessments for characterizing clinical responses. Type 1 responders are more likely to benefit from subsequent pylorus-directed re-treatments, particularly repeat G-POEM interventions. CLINICALTRIALS: gov, Number: NCT04434781.
Keywords: Gastric Emptying Scintigraphy; Pylorus-directed Retreatments; Clinical Failure; Repeat G-POEM; Gastroparesis; Clinical Failure Management; Gastric Peroral Endoscopic Myotomy; G-POEM